Conference Report on the 3rd International Symposium on Lithium Application for Fusion Devices. (14th January 2015) - Mazzitelli, G.; Hirooka, Y.; Hu, J. S.; Mirnov, S.V.; Nygren, R.; Shimada, M.; Ono, M.; Tabares, F.L.
Abstract: The third International Symposium on Lithium Application for Fusion Device (ISLA-2013) was held on 9–11 October 2013 at ENEA Frascati Centre with growing participation and interest from the community working on more general aspect of liquid metal research for fusion energy development. ISLA-2013 has been confirmed to be the largest and the most important meeting dedicated to liquid metal application for the magnetic fusion research. Overall, 45 presentation plus 5 posters were given, representing 28 institutions from 11 countries. The latest experimental results from nine magnetic fusion devices were presented in 16 presentations from NSTX (PPPL, USA), FTU (ENEA, Italy), T-11M (Trinity, RF), T-10 (Kurchatov Institute, RF), TJ-II (CIEMAT, Spain), EAST(ASIPP, China), HT-7 (ASIPP, China), RFX (Padova, Italy), KTM (NNC RK, Kazakhstan). Sessions were devoted to the following: (I) lithium in magnetic confinement experiments (facility overviews), (II) lithium in magnetic confinement experiments (topical issues), (III) special session on liquid lithium technology, (IV) lithium laboratory test stands, (V) Lithium theory/modelling/comments, (VI) innovative lithium applications and (VII) special Session on lithium-safety and lithium handling. There was a wide participation from the fusion technology communities, including IFMIF and TBM communities providing productive exchange with the physics oriented magnetic confinement liquid metal research groups. This international workshop will continue on a biennial basis (alternating with the Plasma–Surface Interactions (PSI) Conference) and the next workshop will be held at CIEMAT, Madrid, Spain, in 2015.